Social networking tools and research information systems: Do they compete? - Sven Bittner (Webology, 2011)
Current developments in the area of research information have led to two different kinds of systems dealing with research-related information: Social networking tools for researchers have reached public attention through reports in mass as well as popular scientific media. Rather hidden from the public focus, universities and governments have pushed the implementation of institutional and national research information systems in recent years. Unquestionably, research information systems and research networking tools show clear similarities, as the data modeled within both system kinds overlaps partially. Nevertheless, the application areas and current uses of these systems differ widely. This paper examines the properties of research information systems and research networking tools. After identifying and taking into account the differences of both system kinds, the paper comes to the conclusion that research information systems and research networking tools currently live in coexistence and will foreseeably do so in the future.